PERBEDAAN PENGARUH GAYA MENGAJAR KONVERGEN DAN DIVERGEN BERBASIS PERMAINAN TERHADAP HASIL BELAJAR LOMPAT JAUH GAYA JONGKOK DITINJAU DARI MOTIVASI BELAJAR SISWA - FATKHUL IMRON (Jurnal Ilmiah Spirit, 2014)
The research objective of this experiment was to determine: (1) differences in the effect of convergent and divergent teaching styles to the learning outcomes of the long jump squat style, (2) the effect of differences in students motivation to learn the results of the long jump squat style, and (3) the interaction effect between the use of teaching styles converge or diverging and students motivation to learn the results of the long jump squat style. To achieve the research objectives have been established, this study conducted experiments to study the design of 2x3 factorial design. The population in this study were fifth grade students of Elementary Schools Ronggowarsito Force Unit VII Department of Education Youth and Sports Laweyan District of Surakarta and then randomized sample generated by 2 Elementary School SDN Bratan I Surakarta as many as 32 students as a group and convergent teaching style of SD Muhammadiyah 11 Mangkuyudan many as 29 students as a group of divergent teaching styles. Then the samples were given a questionnaire that had been tested to determine the validity of students motivation level by classification motivation high, medium and low. Furthermore, given the treatment of learning with each teaching style. Activity data of students in the learning process which includes cognitive, affective and psychomotor assessed using the observation sheet. While the ability of the results of data long jump squat force students gathered to test the ability of measuring the long jump squat style. Data were analyzed using descriptive statistical techniques and inferential statistics . Research results show that: (1) effective teaching style to be applied to converge the subject long jump squat style, especially its role in the achievement of psychomotor domains. Its effectiveness can be seen from the value of student learning outcomes in this group most of the students have reached a value of mastery of learning outcomes as many as 23 students (71.9%) completed and 9 students (28.1%) unfinished, (2) teaching style diverges only has the effectiveness the effectiveness of the cognitive domain and mastery of learning outcomes is still lacking as many as 14 students (48.3%) completed and 15 students (51.7%) was not finished. The average ability of the results of the long jump squat force students who received treatment convergent teaching style is 2.04, while the average-ability students who received treatment 1.83 divergent teaching styles.